Implementasi Metote Story Telling Berbasis Canva Untuk Meningkatkan Daya Ingat Anak Usia Dini - Lisa Aneka Oktapia; Lydia Margaretha; Rika Partika Sari; Evryeni Jusmadi (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study examined the implementation of Canva-based storytelling methods to enhance early childhood memory at TK Amanah, Kaur Regency. Employing a Classroom Action Research (CAR) framework, the investigation followed a cyclical procedure designed to optimize classroom pedagogical interventions. The research participants comprised 15 children enrolled in Group B at TK Amanah, Kaur Regency. The action research was executed across two complete cycles, with each cycle consisting of two sequential sessions. Data analysis combined qualitative descriptive techniques; used to evaluate process improvements represented by criteria predicates and quantitative descriptive analysis to determine performance gains through percentage improvements. The implementation of the Canva-based storytelling method yielded progressive advancements in children's memory retention. Specifically, baseline metrics rose from 33% in Cycle I (Session 1) to 48% in Cycle I (Session 2), expanded to 64% in Cycle II (Session 1), and culminated at 83% in Cycle II (Session 2). In conclusion, the systematic integration of Canva-based storytelling successfully improves early childhood memory capacity, as evidenced by the final benchmark in Cycle II (Session 2) reaching an 83% success rate, which satisfied the